Detección de patógenos en agua de consumo humano mediante la técnica PCR. - Núñez Torres, Darwin Alberto (2023)
In this study, the presence of pathogenic microorganisms such as Listeria monocytogenes, Escherichia coli with its O157:H7 serotype, and Salmonella spp. was determined in human drinking water in the Chambo canton. Selective culture media techniques and conventional Polymerase Chain Reaction (PCR) were employed. Specific primers for each pathogen were used for thermocycling, along with positive controls for contrast. A total of 50 samples from different strategic points in the area were analyzed using these methodologies. Listeria monocytogenes was detected in 40% (20/50) of the samples, Escherichia coli with its O157:H7 serotype in 80% (40/50), and Salmonella spp. in 20% (10/50). Thus, the quality of human drinking water in the canton was determined based on the number of contaminated points with the studied pathogens. With the obtained data, possible alternatives in the sector could be considered to reduce the microbial load in the study matrix.